SHADOW FORMATION IN PERSPECTIVE - Mamurova Feruza Islamovna; Sobirova Sharofat Umedullaevna (International Engineering Journal For Research & Development, 2020)
In particular, future "builders", "architects", "bridge builders" or technicians, engineers & others should become masters of their profession. Today, construction drawing shadows play a major role. Thanks to light and shadow, the architect can show the sophistication of the exterior. Drawings performed in the process of architectural design should be visual and give the most complete picture of the volumetric-spatial structure of the object, compositional solution, the appearance of the building, its plastic solution, surface relief, etc.